$a^3-b^2-b=b^3-c^2-c=c^3-a^2-a=\dfrac{1}{3}$
$\leftrightarrow$ $3a^3=3b^2+3b+1 \\ 3b^3=3c^2+3c+1 \\
3c^3=3a^2+3a+1$
$\leftrightarrow 3a^3=3(b^2+b+\dfrac{1}{3})=3(b^2+b+\dfrac{1}
{4}+\dfrac{1}{12})=3(b+\dfrac{1}{2})^2+\dfrac{1}{4} >0$
$\leftrightarrow a>0$
Không mất tính tổng quát giả sử $a \geq b \geq c >0$ ta có:
$3a^3+b^3=(b+1)^3 \\ 3b^3+c^3 = (c+1)^3 \\ 3c^3+a^3 = (a+1)^3$
$\rightarrow 3c^3+a^3 =(a+1)^3 \geq (b+1)^3 = 3a^3+b^3$
Lại có $3c^3 \leq 2a^3+b^3 \rightarrow 3c^3+a^3 \leq 3a^3+b^3$
$\rightarrow$ đẳng thức xảy ra
Vậy $a=b=c$